Vaccine effectiveness against symptomatic SARS-CoV-2 infection in adults aged 65 years and older in primary care: I-MOVE-COVID-19 project, Europe, December 2020 to May 2021 - Kissling, E; Hooiveld, M; Sandonis Martín, V; Martínez-Baz, I; William, N; Vilcu, A-M; Mazagatos, C; Domegan, L; de Lusignan, S; Meijer, A; Machado, A; Brytting, M; et al. (European Centre for Disease Prevention and Control, 2021)
We measured COVID-19 vaccine effectiveness (VE) against symptomatic SARS-CoV-2 infection at primary care/outpatient level among adults ≥ 65 years old using a multicentre test-negative design in eight European countries. We included 592 SARS-CoV-2 cases and 4,372 test-negative controls in the main analysis. The VE was 62% (95% CI: 45-74) for one dose only and 89% (95% CI: 79-94) for complete vaccination. COVID-19 vaccines provide good protection against COVID-19 presentation at primary care/outpatient level, particularly among fully vaccinated individuals.